Discharging of dust particles of different sizes in an argon afterglow plasma - Denysenko, I.B.; Mikikian, M.; Azarenkov, N.A. (Problems of Atomic Science and Technology, 2022)
The dust charge distribution function (DCDF) in an argon plasma afterglow is obtained by solving numerically the master equation describing dust discharging as a one-step stochastic process. The calculated DCDFs are compared with Gaussian distributions, and it is found that the dust charge distribution functions can be approximated quite well by the latter ones for different external conditions. It is found how the DCDF, mean dust charge, variance and charging time depend on dust size. For late afterglow times, it is also analyzed how the emission of electrons in the collisions of excited argon atoms with dust particles affects the DCDF. It is shown that the emission effect is more essential for larger nanoparticles than for smaller ones.